A preliminary survey of parasites of Malaysian red jungle fowl (Gallus gallus spadiceus) - Babjee, Shaik Mohamed Amin; Lee, Chu Chong; Krishnasamy, M. (Persatuan Doktor Veterinar Malaysia, 1985)
Sixteen red jungle fowls (Gallus gallus spadiceus) were surveyed for the species and prevalence of ecto - and endoparasites in Selangor. The following parasites with the prevalence in brackets were observed: Haemaphysalis wellongtoni (85.7%), Neoschongastia gallinarum (57.1%), Megninia cubitalis (50%), Menopon gallinae (100%), Lipeurus caponis (21.4%), Gonoides dissimilis (14.3%), Plasmodium gallinaceum (50%), Plasmodium juxtanuc1eare (7.1%), Leucocytozoon sabrazesi (7.1%), Heterakis beramphora (100%), Capillaria obsignata (93.8%), Microfilariae (Lemdana sp.) (50%), Oxyspirura mansoni (50%). Lemdana sp. (42.9%), Tetrameres crammi (31.3%), Cheilospirura hamulosa (31.3%), Syngamus trachea (28.6%), Strongyloides avium (6.3%), Mediorhynchus gallinarum (6.3%), Raillietina echinobothrida (68.9%). Amoebotaenia sp. (6.3%), Davainea sp. (6.3%), Tanaisia zarudnyi vietnamensis (62.5%), flukes (Heterophyinae family) (12.5%) and flukes (unidentified) (6.3%). This is a first record of Lemdana sp. in a new host. With the exception of M. gallinarum and T.z. vietnamensis the other nematodes and cestodes have not been reported previously in this host in Malaysia.